Citation study of LIS dissertations for collection development - Yeap, Chun Keat; Kaur, Kiran (Faculty of Computer Science and Information Technology, University of Malaya, 2017)
This study applies citation analysis method to examine the use of information resources by postgraduate students of Master in Library and Information Science (MLIS) in preparing their dissertation at the University of Malaya. References from a sample of 40 MLIS thesis from the period 2000-2005 were examined for: year of publication; author; source title; bibliographic format; language; subject category; and place of publication. Core journal titles are compared with Journal Citation Report (JCR) listing and also for availability at the University of Malaya library. The study shows that journals and books are still the most used sources for information and there is a steady increase in the use of electronic media by LIS researchers. Authorship pattern indicates preference for single authored works. This study serves as a baseline indicator of resources used by LIS researchers. It can be utilised by librarians to focus collection development to support research needs.